THE EFFECT OF ASSET STRUCTURE, COMPANY SIZE AND PROFITABILITY ON CAPITAL STRUCTURE IN BASIC AND CHEMICAL INDUSTRY SUB-SECTOR MANUFACTURING COMPANIES LISTED ON IDX 2014-2017 PERIOD - Tabita Octaria Simanjuntak; Rosdiana Febrina Sari Siregar; Dina Wati Simbolon; Mohd. Nawi Purba (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2020)
The purpose of this study is to test and determine the results of the effect of asset structure, company size andprofitability on capital structure in basic industrial and chemical sub-sector companies listed on the Indonesia StockExchange for the period 2014-2017. In this research, the method used is the quantitative approach method withdescriptive research type and the nature of the research is descriptive explanatory, the data is taken indirectlythrough the website www.idx.co.id. Where the population used is 64 companies resulting in 22 sample companiesusing purposive sampling technique based on certain criteria. The data analysis method used is multiple linearregression analysis. So that the results of the research that has been done on the hypothesis show that partially theAsset Structure and Company Size have no and insignificant effect on Capital Structure, and Profitability has anegative and significant effect on Capital Structure and simultaneously that the three variables have a positive effecton Capital Structure with the coefficient determination of 19.1%.